Rola patriarchatu rabinicznego w późnym antyku - Ciecieląg, Jerzy (Poznańskie Towarzystwo Przyjaciół Nauk, 2014)
The text focuses on the significant role of rabbinical patriarchate in Late Antiquity, in particular in the 4th and in the early 5th century. It discusses the main prerogatives of the patriarch, its legal and ideological foundations. Also, it addresses the relationships between the patriarchate and the Jewish population of Palestine and the Diaspora.
THE ROLE OF RABBINICAL PATRIARCHATE IN LATE ANTIQUITY
The paper aims to present the role and position of rabbinical patriarchate in Late Antiquity, particularly in the 4th and in the early 5th century, the period of its heyday. The author discusses the accounts provided in the sources, including rabbinical literature as well as pagan and Christian writings. Ideological issues occupy a prominent place, with particular attention paid to the claim that the house of Gamaliel II was descended from King David. Lastly, the author presents the relationships between the patriarchs and their courts with the Jews of Palestine and the Diaspora. The paper demonstrates the key role of the patriarchate in the Jewish society in Late Antiquity, which is reflected in the Roman legislation and in the position of the rabbinical patriarch within the imperial administration.
Keywords: Jews; judaism; rabbis; patriarch; Talmud; Sepphoris; Tiberias; diaspora; Palestine; Yavne; apostolos; Exilarch